Sand: Decoupling Sanitization from Fuzzing for Low Overhead - Kong, Ziqiao; Li, Shaohua; Huang, Heqing; Su, Zhendong (Proceedings / International Conference on Software Engineering, 2025)
Sanitizers provide robust test oracles for various vulnerabilities. Fuzzing on sanitizer-enabled programs has been the best practice to find software bugs. Since sanitizers require heavy program instrumentation to insert run-time checks, sanitizerenabled programs have much higher overhead compared to normally built programs. In this paper, we present SAND, a new fuzzing framework that decouples sanitization from the fuzzing loop. SAND performs fuzzing on a normally built program and only invokes the sanitizerenabled program when input is shown to be interesting. Since most of the generated inputs are not interesting, i.e., not bugtriggering, SAND allows most of the fuzzing time to be spent on the normally built program. We further introduce execution pattern to practically and effectively identify interesting inputs. We implement SAND on top of AFL++ and evaluate it on 20 real-world programs. Our extensive evaluation highlights its effectiveness: in 24 hours, compared to all the baseline fuzzers, SAND significantly discovers more bugs while not missing any.